Emotional discourses in young masculinities: the case of young men in Valencia, Spain - Masanet-Ripoll,Erika (2024)
Abstract The aim of this article is to identify the different discourses related to masculinity in young Valencian men based on their narratives about the expression of emotions and feelings and how these are developed in friendship. The research used a qualitative methodology based on focus groups, five groups with young people and one with professionals working with young people. The results of the research allowed us to identify three models of masculinity in relation to the expression of emotions and with the different degrees of emotional connection in friendship relationships: hegemonic masculinity, masculinity in transition and (almost) inclusive masculinity.